(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Explore the knowledge and practice of scoliosis prevention in primary school students of Khmer ethnic parents at 2 primary schools in Tra Vinh province in 2021 Methods: Descriptive cross-sectional study, direct interviews with 402 parents (parents, primary caregivers) of Khmer students at 2 primary schools in Tra Vinh province according to a set of structured questions. Results: The percentage of parents with general knowledge and good practice on preventing scoliosis in students is 46.3% and 40.8%, respectively. The rate of parents’ general knowledge was higher in the group under 30 years old than in the group 50 years old or older (OR = 8.21, 95%CI: 2.49-34.7; p<0.05), Meanwhile, parents whose occupations are officials and civil servants have a significantly higher rate of general practice compared to farmer groups (OR = 8.21, 95%CI: 2.49-34.7). Both general knowledge and practice attainment were significantly higher in the group of parents with high school education or higher than in the group with less than high school education (OR 3.17 and 2.71, respectively; p <0.05). Conclusions: Knowledge and practice of scoliosis prevention among Khmer parents is still limited. It is necessary to implement communication and educational solutions for parents to avoid health problems related to the scoliosis in students.